The Nucleolus of Directed Acyclic Graph Games - Balázs Sziklai; Tamás Solymosi; Tamás Fleiner (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
In this paper we consider a natural generalization of standard tree games where the underlying structure is a directed acyclic graph. We analyze the properties of the game and illustrate its relation with other graph based cost games. We show that although the game is not convex its core is always non-empty. Furthermore we provide a painting algorithm for large families of directed acyclic graph games that finds the nucleolus in polynomial time.
Keywords: C71; 330; Cooperative game theory; Directed acyclic graphs; Nucleolus